Implementation of cognitive-behavioral substance abuse treatment in Sub-Saharan Africa: Treatment engagement and abstinence at treatment exit - Gouse, H.; Magidson, J.F.; Burnhams, W.; Remmert, J.E.; Myers-Franchi, Bronwyn; Joska, J.A.; Carrico, A.W. (PUBLIC LIBRARY SCIENCE, 2016)
Aims: This study documented the treatment cascade for engagement in care and abstinence at treatment exit as well as examined correlates of these outcomes for the first certified Matrix Model1 substance abuse treatment site in Sub-Saharan Africa.